2017
DOI: 10.1590/2237-6089-2016-0070
|View full text |Cite
|
Sign up to set email alerts
|

Association between resilience and posttraumatic stress disorder among Brazilian victims of urban violence: a cross-sectional case-control study

Abstract: Lower levels of resilience, especially the ability to solve situations and having personal values that give meaning to life, immature defense mechanisms, and emotional and physical abuse in childhood are associated with PTSD in adult Brazilian victims of urban violence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 46 publications
1
10
0
2
Order By: Relevance
“…Consistent with other studies, we find high resilience is associated with a low risk of PTSD (Mealer et al., 2017; Mealer, Jones, & Moss, 2012; Mealer, Jones, Newman, et al, 2012; Teche et al., 2017). We used CD‐RISC scale to assess resilience.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with other studies, we find high resilience is associated with a low risk of PTSD (Mealer et al., 2017; Mealer, Jones, & Moss, 2012; Mealer, Jones, Newman, et al, 2012; Teche et al., 2017). We used CD‐RISC scale to assess resilience.…”
Section: Discussionsupporting
confidence: 92%
“…The pattern of associations between PTSD and resilience appears similar across research studies regardless of how resilience is conceptualized and measured. In cross‐sectional studies from a wide variety of countries, resilience has consistently been inversely correlated with PTSD (Duan, Guo & Gan, 2015; Teche et al, 2017; Zang et al, 2017), and it has often been found to moderate or mediate the impact of stress, abuse, neglect or trauma on PTSD severity (Kim, Kim, & Kong, 2017; Lee et al, 2016; Ying, Wu, Lin, & Jiang, 2014). In a longitudinal study of military service personnel, patients with low resilience were at significantly greater odds for developing PTSD, to the degree that the researchers estimated that increasing resilience by 20% could reduce the odds of developing PTSD by 73% and the incidence of PTSD by 32%, with a potential cost savings of 196 million dollars annually (Vyas et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the presence of childhood trauma appears to be a risk factor for the development of PTSD. 9 Although a history of trauma is common in the general population, PTSD is still underdiagnosed. 10 Obtaining an accurate diagnosis is relevant especially in cases with comorbidity, considering suicide risk and trauma history in clinical populations.…”
Section: Introductionmentioning
confidence: 99%